Single‐Chain Magnet Based on Cobalt(II) Thiocyanate as XXZ Spin Chain. Issue 13 (4th February 2020) - Rams, Michał; Jochim, Aleksej; Böhme, Michael; Lohmiller, Thomas; Ceglarska, Magdalena; Rams, Marek M.; Schnegg, Alexander; Plass, Winfried; Näther, Christian
Abstract: Invited for the cover of this issue is the group of Michał Rams at Jagiellonian University (Kraków, Poland) and colleagues at Christian‐Albrechts‐Universität zu Kiel, Friedrich‐Schiller‐Universität Jena, and Helmholtz‐Zentrum Berlin. The image represents a 1D coordination polymer with Co(II) spins that are flipped by photons during an EPR experiment. Read the full text of the article at 10.1002/chem.201903924 . Abstract : " We found that, for this special class of antiferromagnetically ordered SCM compounds, the magnetic relaxations observed in zero field originate mainly from defects and not from (more or less) perfect crystals ." Read more about the story behind the cover in the Cover Profile and about the research itself on page 2837 ff. (DOI: 10.1002/chem.201903924 ).